Perceptions of School Teenagers and Dropouts Towards Sopi Consumption - Hasanah, Venna Ismi Nur; Kiling, Indra Yohanes; Limbu, Ribka (Universitas Nusa Cendana, 2023)
Alcoholic beverages are one type of drink that is often consumed by people of all ages. The behaviour of consuming alcohol among adolescents is still being carried out. In the Province of East Nusa Tenggara (NTT), there is a type of local alcoholic fermented drink, one of which is sopi. This study aims to determine the Perceptions of School Adolescents and School Dropouts on Sopi Consumption in Kelapa Lima District, Kupang City. This type of qualitative research uses the photo-elicitation data collection method. The participants involved in this study were ten teenagers, namely five school teenagers and five school dropouts. The results of the study found five main themes related to knowledge about sopi, emotions felt, reactions, determinants of sopi consumption, and the consequences of sopi consumption.